Analisis Volume Limpasan dengan Metode Green-Ampt - Rena Sempana Wahyu Putri; Dian Sestining Ayu (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
The development of modern era involves the economic, industrial and population growth and also increase of the social needs which cause the increase of the land needs. Land conversion which happens today has a negative impact on the environment and can damage the potency of the land use itself. One of the negative impacts of the land use conversion which are unwell planned, unwell patterned and not aware with the environment is the increased of the run-off volume due to the decrease the ability of the soil infiltration. If there is no further management of the land conversion, it will cause the increase of the annual peak discharge and has the potential to cause the flood. Green-Ampt is one of the method that can be used to analyze run-off volume by estimating capacity and infiltration rate. In Green-Ampt Method there are some parameters that affect the result of the analysis which are related to vegetal cover and soil parameters such as suction head, hydraulic conductivity, initial moisture, and saturated moisture condition of the soil. The aims of this study are to give the additional information and knowledge related to the run-off volume potency in the study area which has been conducted using Green-Ampt Method for the analysis. Hope the result can be used as the reference in management of water resources potency especially in study area, there are Sub Watershed Pogung, Kaloran and Papringan. From the analysis it is known that there is a different result between observed run-off volume and run-off volume by GreenAmpt Method. The difference of the result can occur because of the different intepretation data on both methods. Analysis by observed run-off volume shows that there are run-off for all of the flood event, while the analysis by Green-Ampt Method shows that run-off only occured in one flood event.